Hydrodynamic Sensing Based on Surface-Modified Flexible Nanocomposite Film - 束逸 田禾 王哲 赵海明 米文天 李宇星 曹慧文 任天令 (Chinese physics letters, 2015)
A highly sensitive sensor with piezoresistive nanocomposite material assembled in a flexible composite film is designed and tested for hydrodynamic sensing. Within the device, two nanocomposite films with micrometer scale modified small bumps on the surface are arranged together face-to-face by the interlocking mechanism. These structures are verified to have full-scale piezoresistive high sensitivities which are very appropriate for underwater sensing. Obvious output signals can be observed from the device subjected to the hydroacoustic dipole （vibrating sphere） with exciting frequency from 10 Hz to 40 Hz. A spectral peak can be seen in the Fourier analysis of the output signal at the corresponding frequency.